Nathan A. Berger: aging-cancer and obesity-cancer research require new mechanistic understandings - Li, Brad (Translational Cancer Research; Vol 8, No 2 (April 30, 2019): Translational Cancer Research, 2019)
Aging has been found to be a major risk factor for cancer development. The World Health Organization (WHO) statistics have shown that life expectancy in most developed countries is now exceeding 80 years. Aging population is highly associated with greater health burden, especially in the development of various types of cancers. According to the US National Cancer Institute’s Surveillance Epidemiology and End Results Database, 43% of men and 38% of women will develop an invasive cancer over a lifetime, and more than half of cancers occur in individuals older than 70 (1).